Regulation of a human cardiac actin gene introduced into rat L6 myoblasts suggests a defect in their myogenic program. - Hickey, R (1986)
The rat myogenic cell line L6E9 induces skeletal but not cardiac alpha-actin mRNA upon fusion to form myotubes. However, when a human cardiac alpha-actin gene was introduced into L6E9 myoblasts, differentiation of the cells led to the accumulation of human gene transcripts in parallel with those derived from the endogenous skeletal alpha-actin gene. This result demonstrates that factors which direct rat myogenesis can regulate a muscle gene from another species and that the L6E9 cells may have a defect in their ability to activate endogenous cardiac actin gene expression.